Low Anemia in Pregnancy and Pathology of Cardiovascular Diseases (Negative Complications of Other Diseases) (Eurasian Medical Research Periodical, 2022)
The article includes a variety of experiments, research findings, and recommendations on the causes, complications, and methods for avoiding pregnancy, one of the most pressing issues of our time, as well as possible dangerous cases during this time, disease types and external factors, such as anemia, and the General Pathology of cardiovascular diseases, among other topics.